Binding of some heavy metal ions in aqueous solution with cationized or sulphonylated starch or waste starch. (29th March 2016) - Lappalainen, Katja; Kärkkäinen, Johanna; Rusanen, Annu; Wik, Tiia‐Riikka; Niemelä, Matti; Madariaga, Asier Goitia; Komulainen, Sanna; Keiski, Riitta L.; Lajunen, Marja
Abstract : Contamination of water by heavy metal ions is a severe environmental problem. In this study, starch‐ or waste‐starch‐based binding agents were used to bind heavy metal ions in aqueous solutions in order to prevent the precipitation of metals in alkaline conditions (pH 10). This is a useful feature, e.g . when ultrafiltration is used as a purification technique for a low metal concentration containing wastewaters. The studied binding agents were water‐soluble cationized depolymerized barley starch (CDS) prepared by depolymerization and subsequent cationization, sulphonylated starch (SS) and cationized depolymerized potato peel waste (CW), all of which have not been used previously as binding agents. The studied modified starches were investigated in the binding of Fe(III), Cu(II), Zn(II), or Ni(II) ions in aqueous solutions by utilizing inductively coupled plasma‐optical emission spectrometry (ICP‐OES) as an analytical method. Cationized depolymerized starch bound 80–100% of Fe(III), Zn(II), and Cu(II) ions and SS bound 85–95% of Fe(III), Zn(II), and Ni(II) ions when 0.5 mM metal ions solutions and molar ratio of starch:metal 0.66:1 were used. Cationized depolymerized waste starch bound Cu(II) ions 78–94% (0.25–2.5 mM metal ion solutions prepared with distilled or lake water) in aqueous solution with molar ratio of starch:metal varying from 1:1 to 3:1.